Supervisi Pendidikan dalam Meningkatkan Kualitas Pendidik di Sekolah Menengah atas Balikpapan - Maryanti Maryanti; Yudo Dwiyono; Usfandi Haryaka (Journal on Education, 2023)
Abstract This study aims to describe the planning, implementation, and evaluation of academic supervision in improving the quality of educators at SMA Balikpapan. The approach used is a qualitative approach with the case study method. Collecting data in this study used interviews, observation, and documentation methods involving three informants, namely the school principal, the vice principal for curriculum, and teachers as key informants. Data analysis was carried out through the stages of reduction, presentation, and conclusion. The results of this study indicate that planning for academic supervision involves curriculum assistants and senior teachers formed in a team of school principals' supervisory assistants in carrying out maintenance to streamline educational supervision activities in schools. The implementation of academic supervision for educators has been going quite well; it's just that supervisors still rely on junior teachers and pay little attention to senior teachers with the assumption that senior teachers are experienced, so they don't need to be supervised. Evaluation of process components related to the implementation of academic supervision is very important for the performance of the educational supervision program; this is evidenced by the implementation of visionary leadership starting with conducting pre-class visit activities, conducting class visits, and following up after class visits. Through continued academic leadership, the quality of education can be improved.